Complex effects of habitat amount and fragmentation on functional connectivity and inbreeding in a giant panda population. Issue 2 (20th September 2021) - Connor, Thomas; Qiao, Maiju; Scribner, Kim; Zhang, Jindong; Hull, Vanessa; Bai, Wenke; Shortridge, Ashton; Li, Rengui; Zhang, Hemin; Liu, Jianguo
Abstract: The relationships between habitat amount and fragmentation level and functional connectivity and inbreeding remain unclear. Thus, we used genetic algorithms to optimize the transformation of habitat area and fragmentation variables into resistance surfaces to predict genetic structure and examined habitat area and fragmentation effects on inbreeding through a moving window and spatial autoregressive modeling approach. We applied these approaches to a wild giant panda population. The amount of habitat and its level of fragmentation had nonlinear effects on functional connectivity (gene flow) and inbreeding. Functional connectivity was highest when approximately 80% of the surrounding landscape was habitat. Although the relationship between habitat amount and inbreeding was also nonlinear, inbreeding increased as habitat increased until about 20% of the local landscape contained habitat, after which inbreeding decreased as habitat increased. Because habitat fragmentation also had nonlinear relationships with functional connectivity and inbreeding, we suggest these important responses cannot be effectively managed by minimizing or maximizing habitat or fragmentation. Our work offers insights for prioritization of protected areas. Abstract : Article impact statement : Habitat amount and fragmentation have nonlinear effects on gene flow and inbreeding and are best managed at intermediate levels for pandas. Abstract : Efectos Complejos de la Cantidad de Hábitat y la Fragmentación sobre la Conectividad Funcional y la Endogamia en una Población de Panda Gigante Resumen: Las relaciones entre la cantidad de hábitat y el nivel de fragmentación con la conectividad funcional y la endogamia no son muy claras. Por lo tanto, utilizamos algoritmos genéticos para optimizar la transformación de la superficie de hábitat y variables de fragmentación en superficies de resistencia para predecir la estructura genética y examinamos los efectos de la superficie de hábitat y la fragmentación sobre la endogamia por medio de un método de ventana móvil y de modelado espacial autorregresivo. Aplicamos estos métodos a una población de panda gigante. La cantidad de hábitat y su nivel de fragmentación tuvo efectos no lineales sobre la conectividad funcional (flujo génico) y la endogamia. La conectividad funcional fue más alta cuando aproximadamente 80 por ciento del paisaje circundante era hábitat. Aunque la relación entre la cantidad de hábitat y la endogamia tampoco fue lineal, la endogamia incrementó hasta que casi 20% del paisaje local contenía hábitat, después de lo cual la endogamia decreció a medida que incrementó el hábitat. Debido a que la fragmentación de hábitat tampoco tuvo relaciones lineales con la diversidad funcional y la endogamia, sugerimos que estas respuestas importantes no pueden ser manejadas eficientemente minimizando o maximizando el hábitat o la fragmentación. Nuestro trabajo aporta conocimientos para la priorización de áreas protegidas. 标 题 : 生境面积及破碎化对大熊猫种群功能连通性和近亲繁殖的复杂影响: 摘 要: 野生动物的生境面积和破碎化程度与其种群功能连通性和近亲繁殖之间的关系尚不清楚。因此, 我们以野生大熊猫种群为研究对象, 利用遗传算法将生境面积和破碎化程度优化为阻力面来预测其种群遗传结构, 并基于移动窗口和空间自回归模型来分析生境面积和破碎化对其种群近亲繁殖的影响。结果显示:生境面积及其破碎化程度对其种群功能连通性(基因流动)和近亲繁殖具有非线性影响。当景观面积的 80% 为适宜生境时, 其种群功能连通性最高。虽然生境面积与近亲繁殖之间的关系也是非线性的, 但是当生境面积达到局域景观大约 20%时, 近亲繁殖随生境面积的增加而增加, 然后近亲繁殖水平会随着生境面积的增加而逐渐降低。同时, 由于生境破碎化与功能连通性和近亲繁殖也具有非线性关系, 我们认为不能简单地通过使生境面积最大化或生境破碎最小化来实现对野生大熊猫种群功能连通性和近亲繁殖的有效管理。这项研究也为保护区的优先建立和管理提供科学参考。 关键词 : 生境破碎化, 基因流动, 保护遗传学, 保护生物学, 大熊猫, 景观遗传学, 景观生态学, 遗传多样性, 近亲繁殖